The Poison King : The Life and Legend of Mithradates, Rome's Deadliest Enemy - Mayor, Adrienne, 1946- (Book collections on Project MUSE., 2009)
Machiavelli praised his military genius. European royalty sought out his secret elixir against poison. His life inspired Mozart's first opera, while for centuries poets and playwrights recited bloody, romantic tales of his victories, defeats, intrigues, concubines, and mysterious death. But until now no modern historian has recounted the full story of Mithradates, the ruthless king and visionary rebel who challenged the power of Rome in the first century BC. In this richly illustrated book--the first biography of Mithradates in fifty years--Adrienne Mayor combines a storyteller's gifts with th.